Marriage Law with Stolen Property as Dowry: An Islamic Jurisprudence Perspective through the Lens of Maslahah - Fadlan, Fadlan; Juhani, Hasan Bin; Billah, Muktashim (JURNAL MAHASISWA YUSTISI, 2025)
This study aims to examine: (1) the legal framework of mahar (dowry) in marriage according to Islamic jurisprudence, and (2) the legal implications of using stolen property as mahar, analyzed through the principle of maslahah (public interest). This research employs a library-based methodology, drawing from primary and secondary sources including classical and contemporary fiqh works, Qur’anic exegesis, and scholarly articles. Data collection follows systematic steps of editing, organizing, and concluding, followed by comparative-verificative analysis. Findings reveal that in Islamic law, ownership of wealth is divine in nature (milkiyyah ilahiyyah), carrying moral and legal obligations. Using stolen property, even without direct involvement in theft, is strictly prohibited if its unlawful origin is known. All major Islamic schools agree that stolen property remains the rightful possession of its original owner and must be returned or compensated. Regarding marriage, the majority of scholars assert that the contract remains valid if its other pillars and conditions are met, but the haram mahar is void and must be replaced with an equivalent lawful dowry (mahar al-mithl). The tarjih approach supports this position to uphold the validity of the contract, preserve public interest, and prevent greater harm (mafsadah). The study concludes that the use of haram wealth in dowry is a violation of Islamic principles with moral and social consequences, requiring repentance, restitution, and lawful substitution.